Pelvic Rocking Exercise on The Length of The First Stage of Labor - Erlin Nuraeni; Rukmaini; Shinta Novelia (KHD Production, 2024)
In general, there are still many women in labor who experience a prolonged first stage. Prolonged labor is one of the causes of increased mortality and morbidity in the mother and fetus. There are various methods that can be used to speed up the progress of labor, one of which is using non-pharmacological methods, namely exercise pelvic rocking exercise. The aim of this research is to find out the differences pelvic rocking exercise on the length of the first stage of labor between the experimental group and the control group. Research methods quasi-experiment design. This uses a research design posttest only design with control groups. The population in this study were primigravidarum mothers. The sample in this study consisted of 30 respondents who were divided into 2 groups, namely 15 respondents in the experimental group and 15 respondents in the control group. Research results from independent t-test It is known that the significance value is 0.000 <0.05, so it can be concluded that Ho is rejected and Ha is accepted, which means there is a difference in the length of labor between the experimental group and the control group.pelvic rocking exercise on the length of the first stage of labor. Conclusion there is influence pelvic rocking exercise on the duration of the first stage of labor at the Binuangeun Health Center UPT in 2023. It is hoped that health workers can apply the technique pelvic rocking exercise. This is for mothers giving birth so that mothers can give birth comfortably and in a quicker time compared to previous care.